Sustainable Maritime Human Capital Development: A Quantitative Analysis - Samekto, Agus Aji (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study investigates the quantitative relationship between digital education systems and sustainability competence among maritime students across ten maritime higher education institutions in Asia and Europe from 2019 to 2024. Design/methodology/approach: Using a multiple linear regression model, data were collected through institutional academic records, learning management system (LMS) analytics, and standardized sustainability competence tests, comprising a total of 2,845 valid student observations. Findings: The findings reveal that the integration of digital pedagogy significantly enhances sustainability-related learning outcomes, with competence scores increasing by 29% (p < 0.01). Furthermore, the correlation coefficient between digital education adoption and sustainability competence reached 0.68, indicating a strong positive association. The study demonstrates that digital transformation in maritime education directly supports the development of human capital capable of managing sustainable maritime operations. These results underline the urgency of aligning human resource strategies with digital transition policies in maritime academies to ensure long-term sectoral sustainability. Paper type: Research paper